Assessment of the impact of short-term land use/land cover changes on water resources in the Yanghe reservoir basin, China. Issue 1 (23rd July 2021) - Li, Daming; Bu, Shilong; Chen, Shuo; Li, Qicheng; Li, Yanqing
Abstract: Land Use/Land Cover (LULC) is a main factor that affects the hydrological process of catchments. A better understanding of its influence is of great significance to future land use planning and water resources management. Since 2011, the local government has implemented a land remediation plan, and the LULC in the Yanghe Reservoir Basin has undergone major changes. This paper uses The Soil and Water Assessment Tool (SWAT) model to study blue water (BW) and green water (GW) resources in three typical years (a wet year, dry year, and normal year) under two LULC scenarios in the basin in 2010 and 2017. The results show that from 2010 to 2017, the area of cultivated land and residential construction land increased by 227.28% and 269.23%, respectively; the area of unused land, woodland, and grassland decreased by 98.84%, 35.90% and 39.52%, respectively. Compared with the results of the 2010 LULC scenario, the average BW of the three typical years under the 2017 LULC scenario decreased by 11.66%, 52.32%, and 21.95%, respectively, and the average GW flow increased by 6.72%, 2.90%, and 6.83%, respectively, and the average GW reserves decreased by 14.80%, 11.39%, and 7.67%, respectively. Therefore, this study believes that changes of LULC have led to a significant decrease in runoff and an increase in evapotranspiration in the basin. HIGHLIGHTS: A SWAT model was used to study the blue water and green water resources in three typical years under two LULC scenarios in 2010 and 2017 for the Yanghe Reservoir basin. The increase in the area of arable land in the Yanghe Reservoir basin has led to an increase in the green water coefficient.